Family is a Superpower - Dahl, Michael; Lozano, Omar; DC Comics, Inc. (North Mankato, Minnesota : Capstone Editions, a Capstone imprint, 2019)
"In this DC Comics picture book, the heroic adventures of the Justice League mirror the extraordinary lives of real-life children and their diverse families. With bold illustrations and poetic text, this story makes all families--no matter how big or how small--feel out of this world!"--Jacket.
Keywords: Families -- Juvenile fiction; Superheroes -- Juvenile fiction; Justice League of America (Fictitious characters) -- Juvenile fiction; Families -- Fiction; Superheroes -- Fiction; Justice League of America (Fictitious characters) -- Fiction; Families; Justice League of America (Fictitious characters); Superheroes; Picture books; Fiction; Juvenile works; Picture books